Lithium-ion cell structure based on gel-state electrolyte

CN224934759UActive Publication Date: 2026-11-03XIAMEN LITAI NEW ENERGY TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202522214502.0
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2025-10-20
Publication Date
2026-11-03
Estimated Expiration
2035-10-20

AI Technical Summary

Technical Problem

Existing gel-state lithium-ion cells suffer from unreasonable interface structures, insufficient adhesion between the gel electrolyte and the electrode surface, high interface impedance, and discontinuous ion transport paths, leading to unstable electrochemical performance and potential safety hazards.

Method used

By optimizing the filling and bonding method of the gel electrolyte at the interface between the diaphragm and the electrode, a stable interface layer is formed. By adopting a multi-layer composite diaphragm and in-situ curing process, combined with a secondary liquid injection and re-curing step, a continuous ion transport channel is constructed, which enhances the bonding stability between the electrode and the electrolyte.

Benefits of technology

This achieves a tight bond between the electrode and the electrolyte, reduces interfacial contact resistance, improves the safety and cycle stability of the cell, reduces the risk of lithium dendrite growth and thermal runaway, and enhances electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN224934759U_ABST
    Figure CN224934759U_ABST
Patent Text Reader

Abstract

The utility model relates to lithium ion battery technical field especially relates to a kind of lithium ion cell structure based on gel state electrolyte.A kind of lithium ion cell structure based on gel state electrolyte, including positive sheet, negative sheet, diaphragm and gel electrolyte.The diaphragm is set between positive sheet and negative sheet, gel electrolyte is filled in diaphragm aperture, and in diaphragm both sides respectively with the electrolyte contact surface of positive sheet and negative sheet is pasted, and stable interface layer is formed at pasting place.This interface layer realizes the mutual penetration combination of gel electrolyte and electrode active material, makes ion transmission path continuous, and interface contact impedance reduces.This structure can keep interface stable in the process of charging and discharging, avoid delamination and polarization, improve the cycle stability and security of cell, applicable to the manufacturing field of high energy density battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This utility model relates to the field of lithium-ion battery technology, and in particular to a lithium-ion cell structure based on a gel electrolyte. Background Technology

[0002] With the continuous improvement of the energy density of lithium-ion batteries, the safety and stability of the electrolyte system have become key factors restricting battery development. While traditional liquid electrolyte systems possess high ionic conductivity, their high fluidity and flammability make them prone to leakage and thermal runaway under high temperatures, overcharging, or external impacts, posing significant safety hazards. To address this issue, the industry has gradually shifted its research focus to gel electrolyte systems. Gel electrolytes typically incorporate polymer matrices or gelling components, allowing the electrolyte to maintain high ion mobility while possessing a semi-solid state, thus combining the conductivity of liquid systems with the stability of solid systems.

[0003] However, existing gel-state lithium-ion cells still suffer from unreasonable interface structures. For example, existing literature (hereinafter referred to as Literature 1) with publication number CN115117439B discloses a gel electrolyte battery manufacturing process, in which polymer monomers are incorporated into the electrolyte during battery filling, and then solidified under high temperature and pressure to form a gel electrolyte. Although this scheme reduces electrolyte fluidity and improves thermal stability to some extent, due to the lack of structural design to address the differences in wettability between the separator pores and electrode surfaces, the solidified gel electrolyte does not adhere sufficiently to the electrode surface, and voids or delamination are easily formed locally, resulting in discontinuous electrode-electrolyte interface. As cycling progresses, the interfacial impedance increases, ion transport paths are blocked, leading to enhanced polarization and capacity decay. In addition, this structure lacks a transition layer that can form a stable bond between the electrode and the electrolyte, making it difficult to maintain stable electrochemical performance over a long period. Utility Model Content

[0004] Addressing existing issues such as insufficient adhesion between the gel electrolyte and electrodes, high interfacial impedance, and discontinuous ion transport paths, this invention aims to provide a lithium-ion cell structure based on a gel electrolyte. The design optimizes the filling and adhesion of the gel electrolyte at the separator and electrode interfaces, enabling the gel electrolyte to not only penetrate the separator pores to form a stable filling layer but also form a continuous interfacial layer on the electrolyte contact surface of the electrodes, thus achieving structural integration among the electrode, electrolyte, and separator. This structural design aims to improve ion conduction continuity, reduce interfacial contact impedance, and enhance the overall safety and cycle stability of the cell.

[0005] This utility model achieves the above-mentioned objective through the following technical solution: a lithium-ion battery cell structure based on a gel electrolyte, comprising: Positive electrode, negative electrode, separator, and gel electrolyte; The separator is located between the positive electrode and the negative electrode; The gel electrolyte fills the pores of the membrane and is attached to the electrolyte contact surfaces of the positive and negative electrodes on both sides of the membrane, forming an ion transport channel that connects the positive electrode, the membrane, and the negative electrode. An interface layer is formed at the point where the electrolyte contact surface and the gel electrolyte adhere. The interface layer is continuously connected to the pores of the diaphragm along the thickness direction of the diaphragm to enhance the bonding stability between the electrode and the electrolyte.

[0006] Furthermore, the diaphragm is a multilayer composite diaphragm, comprising: A base film; a ceramic coating disposed on at least one side of the base film; and an oxide solid electrolyte coating disposed on the outside of the ceramic coating and / or on the other side of the base film; wherein the thickness ratio of the ceramic coating to the oxide solid electrolyte coating is (1-5):1.

[0007] Furthermore, the base film is a polypropylene (PP), polyethylene (PE), or PP / PE composite base film with a porosity of 40-50%.

[0008] Furthermore, the positive electrode and / or negative electrode includes a current collector and an active material layer disposed on the surface of the current collector. The active material layer contains inorganic solid electrolyte ceramic particles, and the particle content gradually increases in the thickness direction from the side closer to the current collector to the side farther away from the current collector.

[0009] Furthermore, the electrolyte contact surface is the side of the active material layer away from the current collector, and the particle density of this contact surface is higher than that of the active material layer on the side closer to the current collector, so as to form a stable interface layer when it is bonded to the gel electrolyte. The interface layer includes the bonding region between the inorganic solid electrolyte ceramic particles and the gel electrolyte exposed on the electrode, and the interface layer thickness is 1-5 μm.

[0010] Furthermore, the inorganic solid electrolyte ceramic particles are selected from lithium lanthanum zirconium oxide and / or lithium aluminum titanium phosphate.

[0011] Furthermore, the current collector of the positive electrode is aluminum foil with a thickness of 12-20 μm; the current collector of the negative electrode is copper foil with a thickness of 6-12 μm.

[0012] Furthermore, the oxide solid electrolyte coating is disposed on the side of the separator facing the positive electrode.

[0013] Furthermore, the porosity of the active material layer is 20-35%, and its surface roughness Ra is 0.2-1.5 μm, in order to enhance electrolyte wettability and interfacial bonding.

[0014] A method for preparing a gel solid-state lithium-ion battery cell with a highly dense interface structure includes the following steps: Cell assembly steps: Assemble and package the positive electrode, separator and negative electrode to obtain the cell blank; First electrolyte injection step: Injecting an electrolyte containing gel monomers and initiators into the cell blank as a first electrolyte injection; In-situ curing step: The battery cell that has completed one electrolyte injection is heated and cured, so that the electrolyte is polymerized in situ inside the battery cell to form a three-dimensional cross-linked gel electrolyte; Secondary electrolyte injection step: After the in-situ curing step, liquid electrolyte with a content greater than 0 and not exceeding 30% is added to the cell; Re-curing step: The battery cell that has undergone secondary liquid injection is re-cured so that the replenished liquid and the existing gel network undergo secondary cross-linking and integration, thereby eliminating the free liquid phase at the electrode and / or electrolyte interface and forming a dense and continuous gel electrolyte layer.

[0015] A high-density interface structure gel solid-state lithium-ion battery cell based on in-situ curing and re-curing includes a positive electrode, a composite separator, and a negative electrode stacked sequentially, and a gel electrolyte disposed between the positive and negative electrodes and in contact with the composite separator; wherein: The gel electrolyte is a three-dimensional cross-linked network formed by in-situ polymerization inside the cell. After a secondary liquid injection step to replenish the liquid electrolyte, a re-curing step is performed to integrate it with the existing gel network through secondary cross-linking. The composite membrane uses PP, PE or PP / PE as the base membrane, and at least one side of the base membrane is provided with a ceramic coating and / or an oxide solid electrolyte coating to provide a transition interface for structural support and chemical compatibility during in-situ curing and re-curing. The active material layer of the positive electrode and / or negative electrode contains inorganic solid electrolyte particles, which are selected from at least one of oxide, sulfide or polymer solid electrolytes. The gel electrolyte forms a gradient ion migration channel and a dense bonding layer with the composite membrane and electrode.

[0016] The beneficial effects of this utility model are: This novel lithium-ion battery cell structure fills the pores of a separator with a gel electrolyte, which then fully adheres to the electrolyte contact surfaces of the positive and negative electrodes on both sides of the separator, forming a stable interface layer in the bonding area. This interface layer, microstructurally, represents the interpenetration and intercalation of the gel matrix and the electrode active particles, thereby establishing a continuous ion transport pathway between the electrode and the gel electrolyte. This structural design effectively eliminates contact gaps between the electrode and the electrolyte, resulting in smoother ion migration, significantly reduced interfacial contact impedance, and more stable electrochemical reactions during cycling.

[0017] Compared to the scheme in Reference 1, this design maintains a tight bond with the electrode surface after the gel electrolyte is formed. Due to the excellent flexibility of the interface layer, it can adapt to deformation when the electrode volume changes, thus avoiding interface delamination and ion transport obstruction during charging and discharging. This structure not only improves the electrochemical performance of the battery cell under high-rate operating conditions but also enhances its reliability and safety under high-temperature or long-cycle conditions.

[0018] In summary, this invention forms a stable interface layer at the contact surface between the electrode and the gel electrolyte, making the bonding between the electrode, the separator, and the gel electrolyte tighter and the ion conduction path more continuous. This effectively improves interface stability, suppresses polarization and thermal accumulation, and provides a structural basis for the high safety and high performance of gel-state lithium-ion cells. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the method flow of this utility model.

[0020] Figure 2 This is a schematic diagram showing the cycling curves of a 120Ah gel solid electrolyte and a conventional liquid electrolyte cell with a capacity of 0.5P, as described in one embodiment of the present invention.

[0021] Figure 3 In another embodiment of this utility model, a schematic diagram of the cycling curves comparing a 60Ah gel solid electrolyte with a conventional liquid electrolyte cell of 0.5P is shown.

[0022] Figure 4 This is a schematic diagram of the structure of the composite diaphragm described in this utility model.

[0023] Figure 5 This is a schematic diagram of the structure of the electrode (positive electrode or negative electrode) described in this utility model.

[0024] Figure 6 This is a schematic diagram of the structure of the battery cell described in this utility model. Detailed Implementation

[0025] The technical solutions of the present utility model will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present utility model. Obviously, the described embodiments are only some embodiments of the present utility model, and not all embodiments.

[0026] Among related technologies, lithium-ion batteries, with their high energy density, long cycle life, and environmentally friendly characteristics, have become the core power source for energy storage systems, new energy vehicles, drones, humanoid robots, and 3C consumer electronics, demonstrating enormous market potential. However, this technology still faces safety hazards such as thermal runaway, short circuits, and electrolyte leakage, which seriously hinder the sustainable development of the industry. Among these, the high volatility, flammability, explosiveness, and leakage of traditional liquid electrolytes, as well as the safety risks caused by the uncontrolled growth of lithium dendrites during charging and discharging, are particularly prominent and urgently require improvement and solutions.

[0027] Therefore, such as Figures 1-6 As shown, the embodiments of this application provide a method for preparing a gel solid lithium-ion battery cell with a high-density interface structure and the battery cell itself. Through an in-situ solidification process, the liquid electrolyte can be transformed into a gel electrolyte, constructing a three-dimensional network structure and lithium-ion channels, which has relatively good ionic conductivity. Since there is no liquid electrolyte, the risk of liquid electrolyte leakage can be fundamentally eliminated, effectively reducing safety hazards such as lithium dendrite growth, puncture, and thermal runaway.

[0028] A lithium-ion battery cell includes: a positive electrode, a negative electrode, a separator, and a gel electrolyte. Among these: The positive electrode sheet comprises: a positive electrode material, a conductive agent, a binder, a solvent, and is doped with one of the following solid electrolytes: oxide, sulfide, polymer, etc. The positive electrode material is selected from one of the following: lithium iron phosphate, ternary materials, lithium cobalt oxide, etc. The conductive agent is selected from one of the following: carbon black, conductive graphite, carbon fiber, graphene, etc.

[0029] The negative electrode sheet comprises: a negative electrode material, a conductive agent, a binder, deionized water, and is doped with one of the following solid electrolytes: oxide, sulfide, polymer, etc. The negative electrode material is selected from graphite, silicon-based materials, and metallic lithium; the silicon-based material can be silicon-carbon, silicon-oxygen, or pure silicon, etc. The conductive agent is selected from carbon black, conductive graphite, carbon fiber, graphene, etc.

[0030] The membrane comprises a base membrane layer and a coating layer. The base membrane layer is made of polypropylene (PP) monomer, polyethylene (PE) monomer, or a PP / PE composite, with a porosity of 40-50%. The coating layer is formed by coating the base membrane layer with a solid electrolyte, wherein the solid electrolyte is made of ceramic, PVDF, or one of oxides, sulfides, polymers, etc.

[0031] The gel electrolyte comprises: a solvent, a lithium salt, additives, a gel monomer, and an initiator. Wherein: Solvents include one or more of propylene carbonate, ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, and dimethyl carbonate; Lithium salts, including one or more combinations of lithium hexafluorophosphate, lithium tetrafluoroborate and lithium bis(oxalate)borate, with a concentration of 0.8 to 1.4 mol / L; Additives, including one or more of the following: SEI film-forming additives, flame retardant additives, etc. Gel monomers, including one or more of the following natural polymers such as acrylates, polyethylene glycol, and sodium alginate, are added at a ratio of 0-20%; Initiators, including one or more of the following: free radical type (such as organic peroxides, azo compounds), redox type, photoinitiators, etc., are added at a ratio of 0 to 10%.

[0032] A method for preparing a gel solid-state lithium-ion battery cell with a highly dense interface structure includes preparing a battery cell blank and preparing a gel electrolyte. The battery cell blank is prepared by the following steps: Cathode preparation: Cathode material, conductive agent, binder, and solvent are incorporated into a solid electrolyte, and then the cathode sheet is prepared through processes such as homogenization, coating, rolling, and die-cutting. The cathode material can be one of lithium iron phosphate, ternary materials, or lithium cobalt oxide. The solid electrolyte can be one of oxides, sulfides, or polymers.

[0033] Negative electrode preparation: Negative electrode material, conductive agent, binder, deionized water, and solid electrolyte are incorporated, and then a negative electrode sheet is prepared through processes such as homogenization, coating, rolling, and die cutting. The conductive agent can be one of carbon black, conductive graphite, carbon fiber, or graphene. The negative electrode material can be one of graphite, silicon-based materials, or lithium metal negative electrode. Silicon-based materials can be one of silicon-carbon, silicon-oxygen, or pure silicon. The solid electrolyte can be one of oxides, sulfides, or polymers.

[0034] Membrane preparation: A base membrane with a porosity of 40-50% is prepared using polypropylene (PP) monomer, polyethylene (PE) monomer, or PP / PE composite. A solid electrolyte is then coated onto the base membrane to obtain the separator. The solid electrolyte can be one of ceramic, PVDF, oxide, sulfide, or polymer.

[0035] Core forming: Through processes such as lamination, thermal bonding, welding, packaging, and high-temperature baking, positive electrode sheets, negative electrode sheets, and separators are prepared into battery cells.

[0036] Gel electrolytes are prepared by the following steps: Preliminary steps: Preparation of solvent, lithium salt, additives, gel monomer, and initiator. The lithium salt concentration is 0.8–1.4 mol / L. The gel monomer addition ratio is 0–20%. The initiator addition ratio is 0–10%.

[0037] Electrolyte preparation steps (i.e., preparation method of gel electrolyte): Dissolve lithium salt in an organic solvent according to a certain ratio, and add functional additives such as SEI film-forming additives and flame retardant additives. Stir until homogeneous to obtain a uniform electrolyte solution. Then, add a certain proportion of gel monomers (such as acrylates, polyethylene glycols, or natural polymers) to the electrolyte solution and disperse them fully under stirring conditions. Next, add the appropriate type of initiator (such as organic peroxides, azo compounds, photoinitiators, etc.) and mix evenly to obtain a gel electrolyte that can be injected into the battery cell. This gel electrolyte forms a three-dimensional network structure through in-situ polymerization during the subsequent curing process, thus becoming a dense and stable gel electrolyte.

[0038] The first electrolyte injection step involves injecting the battery cell obtained after the core-forming step with the gel electrolyte obtained in the electrolyte step. Specifically, the battery cell is injected with 70-100% gel electrolyte in one step, then left to stand at room temperature for 12-48 hours, followed by a second standing at high temperature for 12-48 hours, before performing the second electrolyte injection step. The second electrolyte injection step involves two secondary injection processes; one of these processes is chosen for subsequent steps. The secondary injection process includes both high-temperature formation injection and room-temperature formation injection. Only one of these two steps, high-temperature formation injection or room-temperature formation injection, is performed. Specifically: High-temperature formation and liquid injection steps: First, solidify in a high-temperature fixture for 0.5~3h, then convert the liquid electrolyte into a gel electrolyte through thermal initiation, and then perform high-temperature formation, inject 0~30% liquid electrolyte a second time, let stand at room temperature for 12~48h, and then perform a first removal, high-temperature curing, molding, volume division, and OCV testing.

[0039] Room temperature formation and electrolyte injection steps: room temperature formation, secondary injection of 0~30% liquid electrolyte, stand at room temperature for 12~48h, then perform primary removal, high temperature curing for 4h, molding, volume division, and OCV testing.

[0040] For single-injection and two-injection processes, it should also be noted that: In the implementation of this utility model, after the battery cell completes the assembly of the electrodes and separator, it first undergoes a electrolyte injection, injecting 70%–100% gel electrolyte. After the electrolyte injection is completed, the battery cell is left to stand at room temperature for 12–48 hours, and then left to stand at high temperature for 12–48 hours to promote uniform electrolyte penetration. Subsequently, one of two methods can be selected according to different process routes: The first method involves a high-temperature formation and electrolyte injection step. The process begins with high-temperature curing in a fixture for 0.5–3 hours, transforming the liquid electrolyte containing gel monomers and initiators into a gel-state electrolyte through a thermal initiation reaction, thus forming a stable three-dimensional network structure within the cell. High-temperature formation is then performed, involving the first charge-discharge cycle at high temperatures to form stable solid electrolyte interphase (SEI) and cathode electrolyte interphase (CEI) films on the electrode surfaces. Following this, a second electrolyte injection is performed, injecting 0–30% liquid electrolyte to improve the wettability between the electrodes and the separator. After the second injection, the cell is allowed to stand at room temperature for 12–48 hours, followed by electrolyte removal, further high-temperature curing, molding, capacity testing, and open-circuit voltage (OCV) testing, resulting in a stable cell.

[0041] The second method involves a room-temperature formation and electrolyte injection step. The process involves first performing formation at room temperature, completing the initial charge-discharge process without raising the ambient temperature, to gradually form the SEI and CEI films at the electrode interfaces. This is followed by a second electrolyte injection, injecting 0-30% liquid electrolyte and allowing it to stand at room temperature for 12-48 hours to allow for full electrolyte penetration. Next, an electrolyte removal process is performed, followed by high-temperature curing at 60-90°C for approximately 4 hours. Finally, molding, capacity testing, and OCV testing are completed to obtain a qualified battery cell.

[0042] The two different process routes described above allow for flexible selection based on initiator type, capacity design, and application requirements. On one hand, the high-temperature curing followed by formation process is suitable for systems requiring rapid polymerization initiation and ensuring interfacial density. On the other hand, the room-temperature formation followed by overall curing process is more suitable for systems that reduce the risk of early side reactions and gas generation. Regardless of the chosen process route, the ultimate goal is to ensure uniform curing of the gel electrolyte within the cell, forming a dense interfacial structure, thereby achieving high safety and long cycle life.

[0043] In summary, in the embodiments of this invention, different formation paths can be selected for the in-situ solidification process of the gel electrolyte according to actual application requirements. Specifically, two optional process routes are provided: The first process route is "curing first, then forming," which involves heating the liquid electrolyte containing gel monomers and initiators in a high-temperature fixture after initial liquid injection and settling to induce in-situ polymerization, forming a three-dimensional network structure of gel electrolyte. Subsequently, a first charge-discharge formation is performed at a high temperature to rapidly establish the solid electrolyte interphase (SEI) and cathode electrolyte interphase (CEI). The advantages of this process are: the gel electrolyte is cured before forming, resulting in a dense electrode-membrane interface that suppresses electrolyte flow and side reactions, making it more suitable for energy storage cells with larger capacities and thicker electrodes.

[0044] The second process route is "formation first, then curing," which involves initial liquid injection and settling, followed by a first charge-discharge cycle at room temperature to allow the SEI and CEI films to gradually form under a milder environment. This is followed by a second liquid injection and high-temperature curing process to obtain the final stable gel network structure. The advantages of this process are: it avoids severe side reactions caused by high temperatures in the early stages, reduces the risk of gas evolution, and is more suitable for medium-capacity cells or cells with high wettability requirements, such as automotive start-stop power supplies.

[0045] In summary, the two process routes each have their own characteristics and applicable scenarios. During the manufacturing process, the choice can be made flexibly according to the type of initiator, capacity design, and target application environment. Ultimately, both can yield gel solid-state cells with high safety and long cycle life.

[0046] Compared with existing technologies, the gel solid-state lithium-ion battery cell of this invention has high safety. By using an in-situ solidification process to transform the liquid electrolyte into a gel electrolyte, the ionic conductivity is retained, and the battery is also endowed with excellent mechanical and thermal stability. This eliminates the risk of liquid electrolyte leakage and effectively reduces safety hazards such as lithium dendrite growth, puncture, and thermal runaway, providing technical support for improving the intrinsic safety of energy storage, drones, and start-up applications.

[0047] Furthermore, in the lithium-ion battery cell manufacturing process, an electrolyte containing gel monomers and initiators is first injected into the cell, and an in-situ polymerization reaction is triggered in subsequent processes to transform the liquid electrolyte into a gel electrolyte. During the solidification process, this gel electrolyte forms a three-dimensional cross-linked network structure, making the interface between the electrode and the separator more compact and dense, avoiding the porosity and leakage problems present in the liquid electrolyte system. This densification of the interface structure not only improves the stability of the electrode / electrolyte interface but also shortens the diffusion and transport path of lithium ions, thereby achieving a faster ion migration rate and improving the rate performance of the battery cell. Simultaneously, the stability of the interface and the three-dimensional network inhibit the growth of lithium dendrites, effectively reducing the risk of short circuits and thermal runaway caused by dendrites piercing the separator, thus significantly improving the overall safety and cycle life of the battery.

[0048] Furthermore, this invention incorporates a secondary liquid injection process after the initial liquid injection and curing. This involves injecting a specific proportion of liquid electrolyte back into the cured cell. This step improves the wettability of the gel electrolyte in the electrode pores and membrane micropores, enhancing the continuity of ion channels and further improving cycle stability. On the other hand, it effectively solves the process difficulties caused by insufficient or uneven liquid injection during the side-sealing process of traditional gel solid-state batteries, making cell packaging smoother and more reliable. Through the combination of these processes, this invention not only fundamentally eliminates the risks of liquid electrolyte leakage and combustion but also achieves excellent long cycle life and high rate performance while ensuring high safety. (Where SEI refers to the Solid Electrolyte Interphase, mainly formed on the negative electrode surface; CEI refers to the Cathode Electrolyte Interphase, mainly formed on the positive electrode surface; both work together to stabilize the electrode-electrolyte interface.) Example 1: Lithium iron phosphate was selected as the positive electrode material as the active material, supplemented with carbon black conductive agent, carbon nanotube conductive paste (CNT), and polyvinylidene fluoride (PVDF) binder. N-methylpyrrolidone (NMP) solvent was used for homogenization treatment, and an oxide solid electrolyte was added. The positive electrode sheet was obtained after coating, rolling, and die-cutting processes.

[0049] The negative electrode material is artificial graphite, with carbon black conductive agent and carboxymethyl cellulose (CMC) binder added. Deionized water is used as the solvent, and an oxide solid electrolyte is doped into it. The negative electrode sheet is prepared through the same steps. The separator adopts a composite structure, including a 12μm polyolefin-based membrane (polypropylene or polyethylene), with 1–2μm oxide solid electrolyte and ceramic layers coated on both sides to enhance the heat resistance and interfacial stability of the separator.

[0050] The gel electrolyte consists of carbonate solvents (EC / PC / EMC), lithium hexafluorophosphate (LiPF6), film-forming additives, 1–4% acrylate gel monomers, and 0.1–1% azo initiators. The initial electrolyte injection ratio is 70–100% of the total electrolyte volume. After electrolyte injection, the cell is first allowed to stand at room temperature for 12–48 hours, then at a high temperature for another 12–48 hours, followed by high-temperature curing and formation at 60–90°C. Subsequently, 0–30% supplementary electrolyte is injected, and after standing at room temperature, the first electrolyte removal, curing, molding, capacity testing, and open-circuit voltage (OCV) measurement are completed. The resulting cell has a capacity of 120Ah and is intended for energy storage applications. See also... Figure 2 This diagram illustrates the comparison of 0.5P cycle life curves between a 120Ah gel solid electrolyte and a conventional liquid electrolyte cell. Test results show that under 5–8mm steel needle penetration conditions, the cell did not exhibit fire, explosion, or smoke within one hour; after 340 cycles under 0.5P / 0.5P conditions, the capacity retention rate was 99.20%. In contrast, the control cell using a conventional liquid electrolyte caught fire and smoked during the same needle penetration test, and its capacity retention rate after 340 cycles was only 98.27%. This demonstrates that the proposed solution is significantly superior to the conventional liquid system in terms of both safety and cycle life.

[0051] Example 2: The positive and negative electrode fabrication process and separator design are the same as in Example 1, the difference being that the cell design capacity is 60Ah, mainly targeting applications requiring high-rate operation, such as automotive start-stop power supplies. The cell electrolyte injection, settling, and curing processes are the same as in Example 1. The gel electrolyte formulation is also the same, including LiPF6, EC / PC / EMC solvent, film-forming additives, 1–4% acrylate gel monomers, and 0.1–1% azo initiators. The resulting 60Ah cell, in the needle penetration safety test, remained stable for one hour after being punctured by a 5–8mm steel needle, without igniting, exploding, or emitting smoke. See also Figure 3 This diagram illustrates the cycling curve comparison between a 60Ah gel solid electrolyte cell and a conventional liquid electrolyte 0.5P cell. After 340 cycles at 1C / 1C, the capacity retention rate was 96.44%. The control liquid electrolyte cell exhibited fire and smoke during the needle penetration test; although its capacity retention rate reached 99.89% after 340 cycles, its safety performance was significantly insufficient.

[0052] Technical Advantages: First, both types of cells exhibited no fire or smoke in the nail penetration test, while the liquid system cells all showed serious safety hazards, demonstrating a significant improvement in safety. Second, under medium-rate (0.5P) conditions, the capacity retention rate of the novel cell (99.20%) is higher than that of the liquid system (98.27%), showcasing an advantage in cycle life and improved cycle life. Third, under high-rate (1C) conditions, although the capacity retention rate of the gel cell is slightly lower than that of the liquid cell, its inherent safety is far superior to the control group, making it more suitable for start-stop power supplies and drone scenarios with extremely high safety requirements, demonstrating strong application adaptability. The comparison shows that the novel solution has a fundamental improvement in safety, while also possessing a long lifespan advantage in energy storage scenarios, providing a feasible process route for the industrialization of solid-state batteries.

[0053] Based on Reference 1, this invention systematically optimizes the fabrication approach of gel solid-state batteries. The core idea of ​​the gel electrolyte battery fabrication process disclosed in Reference 1 is to add a small amount of polymer monomers and initiators to the electrolyte during the electrolyte injection stage, solidify it at high temperature to form a gel electrolyte, and then add a small amount of liquid electrolyte after formation to improve the wettability of the electrode interface. Although this approach improves safety compared to traditional liquid electrolyte batteries, its fabrication process and interface control still have several fundamental shortcomings.

[0054] First, the gel formation in Reference 1 involves a monolithic heating and solidification process. The liquid electrolyte begins to polymerize before fully penetrating the electrode pores in the initial reaction stage, easily leading to localized gelation or voids. This results in a discontinuous gel layer, interrupted ion conduction pathways, increased internal resistance of the battery cell, and poor cycle consistency. To address this issue, this invention employs an in-situ solidification process. After initial electrolyte injection, the mixture is allowed to stand at room temperature for 12-48 hours, allowing the electrolyte containing gel monomers to fully penetrate the electrode pores and between the membrane fibers. Then, a thermally initiated reaction is performed at 60-90°C, causing the gel to form in situ within the battery cell. This process ensures uniform distribution and dense bonding of the gel electrolyte at the microscale, effectively avoiding the voids and inhomogeneities observed in Reference 1.

[0055] Secondly, Reference 1 involves a liquid replenishment operation after formation to overcome the technical problem that "gaps exist between the gel-like solid electrolyte interface and the electrode interface, preventing sufficient contact and compromising cell performance." While this design temporarily improves electrode wettability, the replenished liquid is not re-solidified, and free liquid can easily form at the interface during long-term cycling. Under high temperature or overcharge conditions, this may lead to side reactions or even thermal runaway. This invention addresses this problem by introducing a secondary liquid injection and re-solidification process. After in-situ solidification, 0-30% liquid electrolyte is added, followed by reheating and solidification. This allows the replenished liquid to re-crosslink and enter the gel network, forming an integrated structure. This fundamentally eliminates the presence of free liquid phases and improves thermal stability and safety performance.

[0056] Furthermore, the diaphragm material commonly used in the first reference is ordinary polyolefin membrane, which has poor thermal stability and insufficient chemical compatibility with the gel electrolyte, easily leading to poor interfacial contact. This invention employs a composite diaphragm design, combining a ceramic layer and an oxide solid electrolyte coating on a polypropylene / polyethylene base membrane. This not only improves the heat resistance and mechanical strength of the diaphragm but also forms a chemical transition layer with the gel system, constructing gradient ion migration channels and significantly improving interfacial bonding.

[0057] Furthermore, Reference 1 did not consider the matching of gel and electrode surface properties. The permeability and adhesion of polymer gels are closely related to the porosity, compaction density, and surface energy of the electrode. The electrode surface in Reference 1 is too dense, like it's been oiled, making it difficult for the gel to penetrate and adhere firmly. Therefore, this invention adds a small amount of solid electrolyte particles to the electrode, making the surface more gel-friendly, allowing the gel to penetrate and adhere tightly without falling off. Specifically, this invention incorporates trace amounts of oxide solid electrolyte particles, such as LLZO (lithium lanthanum zirconium oxide) or LATP (lithium aluminum titanium phosphate), into the positive and negative electrode materials. This increases the surface energy of the electrode, enhances gel affinity, and allows the gel electrolyte to spread evenly and bond firmly after injection, thereby further improving interfacial stability and ion conductivity. LLZO, being a garnet-type solid electrolyte, possesses high ionic conductivity, excellent chemical stability, and high mechanical strength, effectively inhibiting lithium dendrite growth and enhancing the interfacial bonding between the electrode and the gel electrolyte. LATP, a solid electrolyte with a NASICON-type (sodium superionic conductor) structure, exhibits high lithium-ion mobility and good interfacial compatibility, providing a stable ion conduction channel at room temperature. By introducing these inorganic solid electrolyte particles into the electrode, the electrode surface energy is significantly increased, enhancing its affinity for the gel system. This allows the gel electrolyte to penetrate more uniformly into the electrode pores and adhere firmly after injection, thereby further reducing interfacial impedance, improving ion conduction performance, and enhancing the cycle stability and safety of the battery cell.

[0058] Through the above technical means, this utility model forms a complete optimization mechanism from material structure, reaction process to interface coordination: in-situ curing ensures a uniform and dense gel network; secondary liquid injection and re-curing eliminate the risk of free liquid; the composite diaphragm and the solid-particle-doped electrode realize an organic-inorganic synergistic ion-conducting channel. Verification (see [link]). Figure 2 and Figure 3 (and corresponding embodiments). The 120Ah energy storage cell prepared by this invention maintained a capacity retention of 99.20% after 340 cycles at a 0.5P rate, and did not exhibit any fire, smoke, or explosion during the needle penetration test. Therefore, this invention represents a significant improvement over the first reference in terms of gel uniformity, interface stability, and cell safety, demonstrating outstanding inventiveness and industrial application value.

[0059] Additionally, it's worth noting that in the scheme described in Reference 1, during the solidification and formation of the gel electrolyte, "a small amount of conventional liquid electrolyte is added after formation to allow for more complete contact between the gel electrolyte interface and the electrode interface." This fills the gaps between the gel-like solid electrolyte interface and the electrode interface, ensuring sufficient contact and guaranteeing the cell's electrical performance. While this method improves the cell's safety to some extent, its interface structure still has significant defects: the gel layer lacks structural support and an interface transition layer during solidification, leading to pores, voids, or local delamination at the electrode and separator interface, resulting in poor ion channel continuity. Furthermore, the free liquid phase formed after replenishment cannot be re-solidified, making the electrode interface prone to electrochemical instability and thermal runaway risks during long-term cycling.

[0060] To address the aforementioned issues, this invention does not merely improve the material composition in a single aspect, but rather constructs a systematic gel solid-state battery cell structure through the coupled optimization of process pathways and structural design. Its core improvements include in-situ curing processes, a secondary liquid injection and re-curing step, a composite separator structure, and the incorporation of solid electrolyte particles into the electrodes, among other multi-dimensional synergistic methods. The composite separator serves as a crucial bridge for achieving overall stability.

[0061] Specifically, the composite membrane uses a polypropylene / polyethylene (PP / PE) base membrane as the main body, with ceramic coating and oxide solid electrolyte coating on both sides respectively. This design plays a triple synergistic role in the system: 1. The composite membrane provides a flat, stable, and electrolyte-friendly curing surface during the in-situ polymerization of the gel electrolyte, preventing structural collapse and void formation caused by gel shrinkage or local vaporization as described in Reference 1, thus ensuring the uniformity of the gel layer and the density of the interface; 2. The ceramic layer and the oxide solid electrolyte coating (e.g., LLZO or LATP) can form a chemically compatible "gradient transition interface" with the gel system and the electrode surface, reducing interfacial impedance and improving the continuity and directionality of ion transport; 3. When LLZO (lithium lanthanum zirconium oxide) or LATP (lithium aluminum titanium phosphate) particles are incorporated into the electrode, the inorganic oxide layer of the same type in the composite membrane can chemically miscible and mechanically interlock with it in the microstructure, thereby forming a continuous ion-conducting network from the electrode to the gel to the membrane.

[0062] It is precisely because of the introduction of the composite membrane that the in-situ cured gel electrolyte can uniformly polymerize into a dense three-dimensional cross-linked network within a controlled space. The liquid added during the secondary injection and re-curing process can also be completely integrated with the original gel matrix, avoiding the formation of the "free liquid phase" mentioned in Reference 1. If the composite membrane is removed, and only the in-situ curing and secondary injection steps are retained, the curing process will lack stable support and a transition interface. The gel layer is prone to stress shrinkage, cracking, or desorption, which in turn leads to increased interfacial impedance, decreased cycling performance, and reduced safety.

[0063] Therefore, the composite diaphragm design of this utility model has a triple coupling relationship of structure, chemistry, and process with other technical means: ① The composite diaphragm provides a support platform for in-situ solidification; ② The composite diaphragm and the secondary liquid injection process together form wettability and re-crosslinking conditions; ③ The composite diaphragm and the electrode-doped solid electrolyte particles form a chemically compatible system.

[0064] Multiple improvements are interdependent and synergistic, forming a composite gel system with a complete conduction pathway, stable chemical interface and mechanical support structure, rather than a simple superposition of multiple independent features.

[0065] Verified (see) Figure 2 (and its corresponding embodiments), the 120Ah energy storage cell prepared by this utility model has a capacity retention rate of 99.20% after 340 cycles at a 0.5P rate. No fire, smoke or explosion occurred in the needle penetration test of 5 to 8 mm steel needles, which fully verifies the effect of the above-mentioned synergistic mechanism on improving interface stability and intrinsic safety of the cell.

[0066] In summary, this invention represents a systematic upgrade compared to the first reference: in-situ curing achieves uniformity and interface density of the gel layer; secondary liquid injection and re-curing eliminates the risk of free liquid phase and thermal runaway; and an organic-inorganic integrated ion-conducting channel is established through a composite diaphragm and solid-particle-doped electrode, thereby constructing a stable and continuous three-dimensional ion conduction network inside the cell.

[0067] Test results show that the 120Ah gel solid-state battery cell prepared by this invention retains 99.20% of its capacity after 340 cycles at 0.5P rate, and exhibits no fire, smoke, or explosion during the needle penetration test. Therefore, this invention not only achieves substantial progress in the uniformity of the gel electrolyte structure and interface safety, but also forms a completely different collaborative innovation mechanism from the first literature in its overall system design, possessing outstanding creativity and industrial application value.

[0068] In other embodiments: An electrolyte for in-situ gelation of lithium-ion batteries, comprising, by mass percentage: 60-90% solvent, selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dimethyl carbonate (DMC); 8-15% lithium salt, selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), and lithium bis(oxalato)borate (LiBOB); 0.5-8% functional additives, including solid electrolyte interfacial film forming additives and / or flame retardant additives; 1-6% gel monomer, selected from one or more of acrylates, polyethylene glycols, or natural polymers; and 0.2-2.0% initiator, selected from one or more of organic peroxides, azo compounds, redox agents, or photoinitiators; wherein the molar ratio of the gel monomer to the initiator is 5-80.

[0069] Other embodiments: See Figure 4 A composite membrane for in-situ gelled electrolytes includes: a base membrane 131, made of polypropylene (PP), polyethylene (PE), or PP / PE composite, with a thickness of 10-20 μm and a porosity of 40-50%; a ceramic coating 132, disposed on at least one side of the base membrane, the material being selected from at least one of Al2O3, SiO2, or TiO2, with a thickness of 1-3 μm; and an oxide solid electrolyte coating 133, disposed on the outside of the ceramic coating 132 and / or on the other side of the base membrane 131, the material being selected from at least one of LLZO (lithium lanthanum zirconium oxide) or LATP (lithium aluminum titanium phosphate), with a thickness of 1-3 μm; The thickness ratio of the ceramic coating 132 to the oxide solid electrolyte coating 133 is (1-5):1, which is used to provide a transition interface for structural support and chemical compatibility for the gel network during the in-situ gelation of the electrolyte.

[0070] The composite membrane uses a base membrane with a porosity of 40-50% as its main structure. A ceramic coating and an oxide solid electrolyte coating are sequentially formed on its surface, with the thickness ratio of the two controlled at (1-5):1. Controlling the porosity of the base membrane within this range ensures that the gel monomers and electrolyte fully penetrate the membrane channels during the in-situ injection stage, while maintaining good mechanical strength and preventing structural collapse or electrolyte retention due to excessively large pore sizes during the curing and heating stage. The ceramic coating provides skeletal support and thermal protection within the curing temperature range, inhibiting thermal shrinkage and deformation of the base membrane. The outer oxide solid electrolyte coating has high chemical compatibility with the monomer-containing electrolyte system, enabling interfacial bonding with the gel matrix during the in-situ gelation reaction to form a stable chemical transition layer.

[0071] The thickness ratio (1–5):1 is designed to achieve an optimal balance between mechanical support and ion conduction. If the ceramic layer is too thick, it hinders gel penetration; if it is too thin, it cannot provide sufficient thermal stability. By keeping the ceramic layer slightly thicker than the solid electrolyte layer, it ensures that during in-situ gelation, the gel monomers can uniformly penetrate along the pores of the oxide layer and undergo polymerization, thereby forming a dense and continuous adherent gel layer on the electrode surface. This multilayer composite structure enables the membrane to serve both structural support and chemical transition during in-situ gelation and re-curing, effectively eliminating the problems of free liquid phase and micropores at the interface.

[0072] Through the above design, the gel is more evenly distributed on the membrane surface and within the pores, resulting in a stronger interfacial bond and a more continuous ion migration path after curing. This significantly improves the interfacial stability and cycle consistency of the battery cell, and enhances its safety performance under high-temperature environments. This invention achieves a balance between structural density, interfacial coherence, and thermal stability through the synergistic control of base membrane porosity, coating thickness ratio, and material chemical affinity, providing an industrially feasible membrane solution for in-situ gelled electrolyte systems.

[0073] A method for preparing a composite membrane includes the following steps: Base film provision steps: Provide PP, PE or PP / PE base film with a thickness of 10-20 μm and a porosity of 40-50%; Ceramic coating step: A ceramic coating is formed on at least one side of the base film with an aqueous or non-aqueous slurry containing ceramic powder, binder and dispersant. After coating, drying and shaping, a 1-3 μm ceramic layer is obtained. Oxide electrolyte coating step: A slurry containing LLZO or LATP is coated on the outside of the ceramic layer and / or the other side of the base film and dried and shaped to obtain a 1-3 μm oxide solid electrolyte coating. Heat treatment steps: Heat treatment at 80-140℃ for 1-10 min to stabilize the coating structure and improve the interlayer bonding strength; The thickness ratio of the ceramic layer to the oxide solid electrolyte coating is controlled as (1-5):1.

[0074] Other embodiments: See Figure 5 and Figure 6 An electrode for a lithium-ion battery cell includes: a current collector 111; and an active material layer 112 disposed on the surface of the current collector 111. The active material layer 112 contains inorganic solid electrolyte ceramic particles 113, which are distributed in a gradient pattern along the thickness direction of the active material layer 112, gradually increasing in particle content from the side closer to the current collector 111 to the side farther away from the current collector 111. This results in a higher ceramic particle density on the side of the active material layer 112 farther from the current collector 111 than on the side closer to the current collector 111. This allows the side of the active material layer 112 farther from the current collector to form an interface layer 15 rich in ceramic particles after combining with the gel / solid electrolyte 14 or the separator 13, thereby achieving continuous solid-phase contact, reducing interfacial contact resistance, and improving ion migration efficiency. The active material layer 112 is either the positive electrode material layer or the negative electrode material layer of the electrode sheet.

[0075] Electrodes for lithium-ion batteries incorporate inorganic solid electrolyte ceramic particles into the active material layer, with the particle content gradually increasing from the side closest to the current collector to the side furthest away from the current collector along the thickness direction. This creates a ceramic particle-rich interface layer after the electrolyte or separator is applied to the electrode. This gradient design achieves functional partitioning of electron and ion transport paths at the microstructure level: the lower particle content near the current collector maintains good electron conductivity, while the higher particle concentration further away from the current collector enhances compatibility and structural fit with the electrolyte, allowing the electrolyte to form a stable and continuous interface when it penetrates the gaps between the ceramic particles.

[0076] This gradient structure enables a dense solid-phase contact between the electrolyte and the active material layer, effectively filling interfacial voids, continuous ion migration paths, and significantly reduced interfacial impedance. Simultaneously, the ceramic-particle-rich interfacial layer maintains high structural integrity during repeated charge-discharge cycles, preventing the propagation of microcracks caused by electrode material volume expansion, thereby delaying interfacial aging and improving the cycle life and thermal stability of the battery cell. This design not only improves the wettability and bonding strength of gel or solid electrolytes at the interface but also maintains stable ion transport efficiency under high-rate discharge conditions. Overall, this invention achieves structural synergy and performance complementarity between the electrode and electrolyte through gradient control of the active material layer particle distribution, providing a feasible electrode design solution for high-energy-density, high-safety lithium-ion batteries.

[0077] Other embodiments: See Figure 6 A lithium-ion battery cell structure based on a gel electrolyte includes: a positive electrode 11, a negative electrode 12, a separator 13, and a gel electrolyte 14; the separator 13 is located between the positive electrode 11 and the negative electrode 12; the gel electrolyte 14 fills the pores of the separator 13 and is bonded to the electrolyte contact surfaces of the positive electrode 11 and the negative electrode 12 (i.e., the surface of the active material layer 112 away from the current collector 111) on both sides of the separator 13, forming an ion transport channel connecting the positive electrode, the separator, and the negative electrode; an interface layer 15 is formed at the bonding point between the electrolyte contact surface and the gel electrolyte 14, and the interface layer 15 is continuously connected to the separator pores along the thickness direction of the separator 13 to enhance the bonding stability between the electrode and the electrolyte 14.

[0078] The above description is merely a preferred embodiment of this case and is not intended to limit this case. Although this case has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features.

Claims

1. A lithium-ion battery cell structure based on a gel electrolyte, characterized in that, include: Positive electrode, negative electrode, separator, and gel electrolyte; The separator is located between the positive electrode and the negative electrode; The gel electrolyte fills the pores of the membrane and is attached to the electrolyte contact surfaces of the positive and negative electrodes on both sides of the membrane, respectively. An interface layer is formed at the point where the electrolyte contact surface and the gel electrolyte adhere.

2. The lithium-ion cell structure based on gel electrolyte according to claim 1, characterized in that, The diaphragm is a multi-layered composite diaphragm, comprising: Base film; A ceramic coating is disposed on at least one side of the base film; and An oxide solid electrolyte coating is disposed on the outside of the ceramic coating and / or on the other side of the base film; The thickness ratio of the ceramic coating to the oxide solid electrolyte coating is (1-5):

1.

3. The lithium-ion cell structure based on gel electrolyte according to claim 2, characterized in that, The base film is a polypropylene, polyethylene, or PP / PE composite base film, and its porosity is 40-50%.

4. The lithium-ion cell structure based on gel electrolyte according to claim 1, characterized in that, The positive electrode and / or negative electrode includes a current collector and an active material layer disposed on the surface of the current collector. The active material layer contains inorganic solid electrolyte ceramic particles, and the particle content gradually increases from the side closer to the current collector to the side farther away from the current collector in the thickness direction.

5. The lithium-ion cell structure based on gel electrolyte according to claim 4, characterized in that, The electrolyte contact surface is the side of the active material layer away from the current collector. The particle density of this contact surface is higher than that of the active material layer on the side closer to the current collector, which is used to form a stable interface layer when it is bonded to the gel electrolyte. The interface layer includes the bonding region between the inorganic solid electrolyte ceramic particles and the gel electrolyte exposed on the electrode, and the interface layer thickness is 1-5 μm.

6. The lithium-ion cell structure based on gel electrolyte according to claim 1, characterized in that, The current collector of the positive electrode is aluminum foil with a thickness of 12-20 μm; the current collector of the negative electrode is copper foil with a thickness of 6-12 μm.

7. The lithium-ion cell structure based on gel electrolyte according to claim 4, characterized in that, The active material layer has an open porosity of 20-35% and a surface roughness Ra of 0.2-1.5 μm to enhance electrolyte wettability and interfacial bonding.

Citation Information

Patent Citations

  • A manufacturing process for gel electrolyte battery

    CN115117439B